2014
DOI: 10.9790/2402-08921216
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic evaluation of soy-groundnut paneer

Abstract: Soybean is an excellent source of protein and fat. However, beany flavour, indigestible components and anti-nutritional factors present in soybean pose obstacles in utilization of soybean. Soyapaneer one of the most nutritional products can be prepared from soymilk. Soypaneer contain 14 per cent proteins, 3.6 % fats and about 72 per cent moisture content. Milk paneer, though it is popular, but it is expensive costing Rs.300/kg. Hence it is out of economy to reach the majority of Indian people. In this context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…As noted above, the literature repeatedly describes beany flavor and gritty mouthfeel to be “off characteristics” and undesirable in soy products. These studies suggest that modifying fermentation, processing, or blending other plant-based milks approaches improves these sensory characteristics [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. It is described that beany and gritty sensory attributes are reduced; however, no study directly measured these attributes during sensory analysis.…”
Section: Review Of the Sensory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, the literature repeatedly describes beany flavor and gritty mouthfeel to be “off characteristics” and undesirable in soy products. These studies suggest that modifying fermentation, processing, or blending other plant-based milks approaches improves these sensory characteristics [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. It is described that beany and gritty sensory attributes are reduced; however, no study directly measured these attributes during sensory analysis.…”
Section: Review Of the Sensory Methodsmentioning
confidence: 99%
“…Khodke et al [ 21 ] created six soft PBCS at varying ratios of soy to groundnut (a legume crop formally known as peanut) milk in order to reduce the naturally occurring beany flavor of soymilk. Results of a hedonic evaluation (9-point hedonic scale) performed by 10 trained participants indicated the 90:10 soy/groundnut ratio received the highest acceptability rating compared to other ratio blends, including PBCS control, in terms of color, flavor, appearance, texture, and taste.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though soya-based DFICs have been investigated by many scholars (Hofmann and Marshall, 1985; Chumchuere et al , 2000; Noh et al , 2005; Ifesan and Oguntoyinbo, 2012; Li et al , 2013; Adejuyitan et al , 2014; Khodke et al , 2014; Lorrungruang et al , 2014; Murugkar, 2014; James et al , 2016; Li et al , 2017), it was found that most of the commercial DFICs sold in the UK were coconut-oil-based (74%) and only 3% of them were soya-based. By the time this paper was written, no scientific articles on coconut-oil-based DFICs had been published; however, patents on DFIC manufacturing processes mention this ingredient (Holz-Schietinger et al , 2014; Bergsma, 2017, Grzanich et al , 2017; Tedesco, 2018; Yehezkeli and Langiel, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Adejuyitan et al (2014) produced DFICs using different soya milk to coconut milk ratios; they found that the most accepted sample was that featuring the highest proportion of coconut milk (50%w/w). Similarly, Khodke et al (2014) employed different proportions of soya milk and peanut milk to prepare DFICs; overall, the sample containing 90%w/w soya milk and 10%w/w peanut milk was the most preferred by the sensory evaluation participants, followed by the sample containing only soya milk. Ifesan and Oguntoyinbo (2012) prepared various DFIC samples by combining sesame milk and soya milk at different ratios; the product containing only soya milk obtained the highest overall sensory score.…”
Section: Introductionmentioning
confidence: 99%
“…The groundnut is particularly valued for its protein content having high biological value (Khodke et al . ).…”
Section: Introductionmentioning
confidence: 97%